2011
DOI: 10.1002/pssr.201105359
|View full text |Cite
|
Sign up to set email alerts
|

Ferrimagnetic ZnFe2O4 thin films on SrTiO3 single crystals with highly tunable electrical conductivity

Abstract: Within the current search for spintronic materials with spin polarized electronic conductivity, the spinel-type ferrite materials gain more and more interest due to their comparably high intrinsic magnetic moments that are based on strong antiferromagnetic superexchange interaction between A and B ions. In case of normal spinels as for example ZnFe 2 O 4 (ZFO), additional disorder on the tetrahedral (A-Zn 2+) and octahedral ) lattice sites leads to effective ferrimagnetism.Suzuki [1,2] further pointed out tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 10 publications
0
32
0
Order By: Relevance
“…An interesting coincidence is that the highest ZFA was also observed in doped ferrite having flattened grains. Another interesting example is given by Lorenz et al [37] where they had shown the possibility to control conductivity at 300 K with pulsed laser deposition conditions for ZnFe 2 O 4 spinels. The differences in microwave behaviour of MÀI and MÀII MNPs can be used in the design of multilayered microwave radiation absorbing structures having different nanoparticles as fillers of different layers.…”
Section: Magnetic Propertiesmentioning
confidence: 97%
“…An interesting coincidence is that the highest ZFA was also observed in doped ferrite having flattened grains. Another interesting example is given by Lorenz et al [37] where they had shown the possibility to control conductivity at 300 K with pulsed laser deposition conditions for ZnFe 2 O 4 spinels. The differences in microwave behaviour of MÀI and MÀII MNPs can be used in the design of multilayered microwave radiation absorbing structures having different nanoparticles as fillers of different layers.…”
Section: Magnetic Propertiesmentioning
confidence: 97%
“…Angular dependent measurements of the reflections of SrTiO 3 (311) and (Mn,Zn)Fe 2 O 4 (511) were carried out showing only parallel orientations of the layer to the substrate, which is similar to the behavior of ZnFe 2 O 4 on SrTiO 3 . 17,23,24 It can be speculated that this epitaxial growth is possible due to a large dislocation density at the interface that subsides throughout the film and causes a gradual change of the lattice constant within a few layers.…”
Section: Resultsmentioning
confidence: 99%
“…11 Because of the lattice mismatch and the possible diffusion of titanium into the layer, the magnetic properties of the layer are reported to differ from the bulk properties. 6,9,[15][16][17][18][19] Nevertheless, it was still possible to grow layers directly on SrTiO 3 without such buffer layers although the layers exhibited lattice parameters pointing to a large strain, which might be the reason of the variations in the films. Additionally, ferrites grown without buffer layers have shown magnetic properties, which makes them interesting candidates for various applications.…”
Section: -11mentioning
confidence: 99%
See 2 more Smart Citations